TRANSLATION DIFFICULTIES IN TEACHING PROCESS - Normurodova Mohinur (Journals Park Publishing, 2022)
This artice focuses specifically on syntactic difficulties in translation, but issues in translation can manifest itself on different linguistic levels. In this section article summarises relevant literature in the field of (human) translatability.
Keywords: translation, complementary, translatability, translation problems, translation distortions